Alkali treatment to transform natural clinoptilolite into zeolite Na–P: Influence of NaOH concentration. (September 2022) - Wang, Cheng; Yu, Jiale; Feng, Kai; Guo, Huidong; Wang, Lipeng
Abstract: In this study, natural clinoptilolite was treated with NaOH solutions of different concentrations under mild ambient conditions. The composition and structure of the as-prepared samples were characterized, and their performance was assessed in terms of the removal of the heavy metal ions Cd 2+, Cu 2+, and Cr 3+ from the aqueous solution. The results showed that the composition, structure, and capability of removal of heavy metal ions of the samples were significantly influenced by the NaOH concentrations. The crystal structure of clinoptilolite remained invariant under a relatively low NaOH concentration (≤0.5 M), began transforming into zeolite Na–P under a medium NaOH concentration (∼1.0 M), and then completely transformed into it under a high NaOH concentration (2.0–4.0 M). The samples treated with NaOH had lower SiO2 /Al2 O3 ratios, and were superior to unmodified natural zeolite in removing the heavy metal ions. This method of treatment with relatively high concentrations of NaOH is a simple and effective way to transform natural clinoptilolite into the zeolite Na-P rich ion exchanger, which is suitable for removing heavy metal ions. Graphical abstract: Image 1 Highlights: Natural clinoptilolite was treated using NaOH solutions with different concentrations. Structure of clinoptilolite basically maintained invariably under ≤0.5 M NaOH concentrations. Clinoptilolite completely transformed to zeolite Na–P under 2.0–4.0 M NaOH concentrations. Zeolite Na–P rich ion exchanger had excellent heavy metal ion removal performance.